ORGANIZATIONAL AND ECONOMIC SUPPORT FOR THE MANAGEMENT OF THE DEVELOPMENT OF HUMAN CAPITAL IN THE DIGITAL ECONOMY - Ulugmuradova Nodira Berdimuradovna (Labor economics and human capital, 2023)
This article explores the exchange of information based on innovative technologies, based on its dissemination, and its theoretical description, a structure that allows relationships between many companies.